1995
DOI: 10.1021/bi00020a037
|View full text |Cite
|
Sign up to set email alerts
|

Putative Blue-Light Photoreceptors from Arabidopsis thaliana and Sinapis alba with a High Degree of Sequence Homology to DNA Photolyase Contain the Two Photolyase Cofactors but Lack DNA Repair Activity

Abstract: The putative blue-light photoreceptor genes of Arabidopsis thaliana and Sinapis alba (mustard) are highly homologous to the DNA repair genes encoding DNA photolyases. The photoreceptors from both organisms were overexpressed in Escherichia coli, purified, and characterized. The photoreceptors contain two chromophores which were identified as flavin adenine dinucleotide and methenyltetrahydrofolate. This chromophore composition suggests that the blue light photoreceptor may initiate signal transduction by a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
251
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(255 citation statements)
references
References 20 publications
3
251
1
Order By: Relevance
“…Because of the high sequence and structural similarities between photolyase and CRY, it is generally assumed that CRYs have the same two cofactors as well. However, no CRY has been purified to date from its native source and those that have been purified as recombinant proteins contain FAD to varying levels and either trace amounts of MTHF or none at all (Lin et al 1995;Malhotra et al 1995;Özgür and Sancar 2003;Song et al 2007). Hence, formal proof that CRYs contain MTHF, or any other secondary chromophore, is lacking.…”
Section: Structures Of Photolyase and Cryptochromementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high sequence and structural similarities between photolyase and CRY, it is generally assumed that CRYs have the same two cofactors as well. However, no CRY has been purified to date from its native source and those that have been purified as recombinant proteins contain FAD to varying levels and either trace amounts of MTHF or none at all (Lin et al 1995;Malhotra et al 1995;Özgür and Sancar 2003;Song et al 2007). Hence, formal proof that CRYs contain MTHF, or any other secondary chromophore, is lacking.…”
Section: Structures Of Photolyase and Cryptochromementioning
confidence: 99%
“…No native CRY has been purified to date due to their low abundance; instead, the CRYs have been expressed as recombinant proteins using bacterial, insect, or mammalian cells. CRYs purified in this manner contain little to no MTHF chromophore (Lin et al 1995;Malhotra et al 1995;Hsu et al 1996;. With respect to flavin content, CRYs fall into two groups.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…As hy4 mutants are primarily deficient in their response to B, we had originally proposed that the second chromophore for CRYl was likely to be a deazaflavin (Ahmad & Cashmore 1993). However, it has been demonstrated that a fusion protein between the 'photolyase' domain of CRYl and maltose-binding protein binds a pterin when expressed in E. coli (Malhotra et al 1995). The precise nature of the CRYl second chromophore in Arabidopsis remains to be detemiined.…”
Section: The Ehromophores Of Crylmentioning
confidence: 99%
“…Class I DNA-photolyases repair cyclobutane pyrimidine dimers by using light energy in the UV-A/blue region (for review see Sancar, 1994). CRY1 and the SA-PHR1 protein from white mustard (Batschauer, 1993), which is 89% identical with Arabidopsis CRY2, bind the chromophores typically present in photolyases, but have no photolyase activity Malhotra et al, 1995). The hy4 mutant is only affected in some blue light responses (Ahmad and Cashmore, 1993;Ahmad et al, 1995;Bagnall et al, 1996;Koornneef et al, 1980), indicating the presence of further blue light receptors in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%